Exploring Phosphorus Dynamics in Submerged Soils and Its Implications on the Inconsistent Rice Yield Response to Added Inorganic Phosphorus Fertilisers in Paddy Soils in Sri Lanka - Palihakkara J; Burkitt L; Jeyakumar P; Attanayake CP (Massey University, 2024)
Rice is the primary energy source of more than half of the global population. Challenges persist in managing phosphorus (P) in paddy soils of tropical rice-growing countries. In Sri Lanka, one specific challenge is the inconsistent yield response observed when inorganic P fertilisers are applied to paddy soils. Previous research conducted in Sri Lanka has shown that the rice yield response to added P fertilisers cannot be adequately explained by factors such as soil available P, irrigation schemes, soil texture, pH, electrical conductivity, total carbon content and available Fe and Mg concentrations. Due to the submerged conditions in which rice is grown for a significant portion of its lifespan, a unique environment controlled by redox-driven processes is developed in paddy soils. Therefore, releasing P from submerged soils is an outcome influenced by complex hydrological and biogeochemical processes, strongly influenced by inherent soil characteristics. The present review paper aimed to critically examine existing literature on soil P behaviour in submerged paddy soils of Sri Lanka, to clarify the behaviour of P under submergence, identify the factors affecting such behaviour and highlight the research gaps that need to be addressed, in order to effectively manage P in the paddy soils of Sri Lanka.